Quality of Life in an Urban Environment: A Typology of Urban Units of Olomouc - Kladivo, Petr; Halás, Marián (Quaestiones Geographicae, 2012)
Studying the internal structure of cities is one of the traditional topics of geographical research. The aim of this article is to show a possible approach to the study of an objective dimension of the quality of life in an intra-urban environment focusing on detailed studies of selected indicators of the quality of life. There exist many approaches to evaluating the quality of life because it is an interdisciplinary term; we are going to focus on this issue in terms of the quality of living conditions. Using multivariate statistical methods, we are going to try a typology of an urban area in just those terms, and the results will be confronted with the perception of the quality of life by residents themselves. The area studied will be the city of Olomouc.